DEVELOPMENT OF THE ENTERPRISE PRODUCTION SYSTEM BY ORGANIZATIONAL CULTURE RESOURCES - D. V. Shkolnyi (Вестник университета)
Organizational culture is the driving force behind the transformation of the enterprise. Effective improvement of production systems of industrial enterprises is based on the use of organizational culture resources. The development of the production system is an ongoing process based on such key elements as the management system, management processes and organizational culture. The quintessence of such development is the formation of the cultural shell of the enterprise and the establishment of ideal production, where people are the only active resource, since without them self-development is impossible. The stages of applied measures to improve the production system with various resources that include key development elements: the management system and processes, the formation of a system for collecting, analyzing and using best practices in order to increase the competitiveness of the enterprise, building a self-developing system of continuous improvements, creating an organizational culture that allows maximize the potential of employees and develop their abilities, have been considered in the article. Each stage of the development of PSP must pursue a goal of forming a loyal team.